PENGARUH PARTISIPASI ANGGARAN, ASIMETRI INFORMASI, KOMITMEN ORGANISASI, DAN KETIDAKPASTIAN LINGKUNGAN PADA SENJANGAN ANGGARAN - Kadek Erna Yuliantari Putri; Sang Ayu Putu Arie Indraswarawati (Hita Akuntansi dan Keuangan, 2020)
Budgetaryi sector budgetingi is an instrumenti of accountabilityi for managingi public fundi managementi and for implementingi programsi funded by publici money. This researchi was carried out iin the OPD in Klungkungii Regency. Data collectioni is done by givingi questionnaires. The studyi populationi was 174 people. Teknikii determines the samplei using the Purposivei Sampling Formula. Data analysisi was performed withi multiple lineari regression analysis. Fromi the resultsi of the research, it is knowni that there is an influencei on budgetary participationi in dealing withi the budgetaryi agreement and fromi the results of the researchi asymmetryi of information thati does not have an influencei on the budgetaryi dealings, from the resultsi of the research, it is knowni that there is an influencei on the organizationis budgetaryi agreement andi from the results of researchi on informationi asymmetry.